RANCANG BANGUN SISTEM INFORMASI PENERIMAAN SISWA BARU PADA SMK BUDHI WARMAN 1 JAKARTA - Ruhul Amin (LPPM Nusa Mandiri, 2017)
System acceptance of new students that are used today by SMK Budhi Warman 1 still using manual systems, where the committee registration data entry by recording the books, authors, therefore, intends to make the information system admission of new students web-based SMK Budhi Warman 1. Making the information system admission of new students using the web-based PHP programming language and MySQL database. The registration system is web-based SMK Budhi Warman 1 Jakarta can be easier for potential new students to register to save time and cost than if it comes directly to the school and with the information system of information admission of new students, are expected to assist and simplify the processing of learners SMK Budhi Warman 1 Jakarta.